Desain Didaktis Kemampuan Literasi Matematika Siswa Dalam Materi Persamaan Linear Berdasarkan Perbedaan Gender - Annastyah Nur Husnul; Andi Kusumayanti; Andi Halimah (Department of Mathematics Education, 2025)
Mathematical literacy skills are an important competency in the 21st century, but they are still relatively low in various educational units. In addition, gender differences often affect students' thinking styles, learning processes, and achievements in mathematics. Therefore, a learning design that is responsive to variations in learning needs based on gender is needed. This research aims to develop a didactic design that can improve the mathematical literacy ability of class X students of SMA Negeri 8 Bone on linear equation material by considering gender differences. The research approach uses Didactical Design Research (DDR) which consists of three stages: prospective analysis, metapedadidactic analysis, and retrospective analysis. The research subjects were students of class X.8 who were selected based on the results of literacy tests and interviews. The results of the study showed that there was a difference in the characteristics of learning obstacles between male and female students. Male students tend to experience obstacles in the aspects of accuracy and algebraic operations, while female students face more difficulties in the final proof and representation stages. Local context-based didactic design and adaptive literacy strategies have proven to be effective in facilitating conceptual understanding and problem-solving skills across the board. In addition, students' responses to LKPD are positive because they are considered to help understand the material contextually and interactively. This research contributes to the development of a mathematics learning design that is more adaptive to gender differences and is able to anticipate learning barriers that may arise.